Sources, spectral characteristics, and fluxes of dissolved organic matter in coastal groundwater and river water in western Guangdong, China - Wang, Chao; Hu, Xuanyu; Liu, Yilin; Jin, Guangzhe (Frontiers in Environmental Science, 2022)
Groundwater discharge and river runoff are two important ways for allochthonous dissolved organic matter (DOM) to enter the ocean, but they vary spatially. Currently, the source, composition, and efflux of groundwater and riverine DOM to the tropical northern South China Sea remain poorly understood, preventing an accurate estimate of coastal carbon budgets. In July 2021, nine groundwater and six river water samples were collected along the coast of western Guangdong and were characterized using dissolved organic carbon (DOC) analysis, UV-visible, and fluorescence spectroscopy techniques. Atypical absorption spectra were strongly observed in groundwaters, which were mainly attributed to the high-level nitrates. An exponential-Gaussian equation showed that the average contribution of nitrate to total groundwater absorbances was up to 36% at ~ 300 nm. Groundwater showed lower levels of DOC, colored DOM (CDOM), and fluorescent DOM (FDOM) as compared to river water, whereas the humic-like components dominated both groundwater and river water FDOM pools. Higher values of spectral slope S350–400, fluorescence index, biological index, and the ratio of two humic-like fluorescence jointly reveal that groundwater DOM mainly originated from microbial activities, whereas the river water DOM had considerable contribution from terrestrial soil. High precipitation, natural or agricultural land types, and a lack of seawater intrusion are expected to cause low levels of groundwater DOM in western Guangdong. Among 52 rivers from across the globe, high watershed productivity and precipitation may lead to high–moderate DOM levels in river water in western Guangdong. The DOM fluxes via fresh groundwater discharge in western Guangdong are comparable in magnitude to those by river runoff, accounting for 16%–18% of the Pearl River DOM fluxes. Based on the slopes of linear correlations between CDOM and DOC obtained in groundwater samples and 52 rivers, as well as the data on water fluxes and DOC levels, the global CDOM fluxes via groundwater discharge and river runoff are estimated to be 3.5–12.2 × 1012 m2 yr−1 and 4.3 ± 0.3 × 1014 m2 yr−1, respectively, highlighting the importance of considering groundwater discharge and river runoff in coastal carbon budgets.